Use cases for stationary battery technologies: A review of the literature and existing projects. (April 2016) - Malhotra, Abhishek; Battke, Benedikt; Beuse, Martin; Stephan, Annegret; Schmidt, Tobias
Abstract: In electricity systems with a high penetration of wind and solar power generation, electricity storage can be employed to balance power supply and demand. In recent years, stationary batteries are receiving a particularly high degree of attention as they can be used to provide several services in modern electricity systems. However, while a rising number of such battery systems are deployed globally, academic literature has not addressed the trends in deployment of these battery technologies. Thus, this study strives to address this gap by identifying and describing the most attractive use cases for stationary battery technologies on mainland and island electricity systems in two steps. First, the existing literature on applications, profitability and use cases of battery technologies has been reviewed. Second, based on analyses of a database of battery installations and of 26 interviews with industry and academia experts, the six most prevalent use cases have been identified and are presented in this paper. We describe these use cases in detail, highlighting their drivers, sources of value creation and risks.